Efficacy of Triple Antibiotic Paste, Moxifloxacin, Calcium Hydroxide And 2% Chlorhexidine Gel In Elimination of E. Faecalis: An In vitro Study - Ashik Ali Lakhani; K.S Sekhar; Pankaj Gupta; Bellam Tejolatha; Anjali Gupta; Shruti Kashyap; Veena Desai; Shanin Farista (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Root canal treatment is incomplete without usage of intra canal medicaments. They help in the reduction of bacterial count and its by-products, making canals clean and decreasing postoperative pains. Aim: The aim of this study was to evaluate and compare the antimicrobial activity of triple antibiotic paste, Moxifloxacin, calcium hydroxide and 2% Chlorhexidine (CHX) gel in elimination of Enterococcous faecalis (E. faecalis). Materials and Methods: Seventy-five root blocks were obtained from extracted single rooted human teeth. The canal diameter was increased using Gates- Glidden drill up to size 3 and then contaminated with E. faecalis for 21 days. The contaminated samples were then divided into following 5 groups. Group 1: Saline (negative group), Group 2: Calcium hydroxide Ca(OH)2 , Group 3: 2% CHX gel, Group 4: Triple Antibiotic Paste (TAP) (50 μg – metronidazole of 400 mg, 50 μg – minocycline of 100 mg, 50 μg – ciprofloxacin of 100 mg) and Group 5: Moxifloxacin (50 μg – moxifloxacin of 400 mg). Dentin debris was obtained at the end of first, 7th, and 10th day using Gates Glidden drill sizes 4 and 5. The bacterial load was assessed by counting the number of Colony Forming Units (CFUs). The data were analyzed with the ANOVA and Post-Hoc tests to assess the differences in antibacterial efficacy between groups (p=<0.001). Results: A 2% CHX gel alone completely inhibited the growth of E. faecalis after one, seven and 10 days. The 2% CHX gel was the most effective medicament against E. faecalis, as it showed significant differences with normal saline, calcium hydroxide, Moxifloxacin or triple antibiotic paste at all time intervals. The triple antibiotic paste group showed a moderate antibacterial effect as its difference with all group was significantly better at all days. Moxifloxacin was more effective than calcium hydroxide on 7th and 10th day. Conclusion: Best antimicrobial efficacy was shown by 2% CHX gel. Moxifloxacin was equally efficient compared to triple antibiotic paste against E. faecalis at longer intervals of time.